DATA-DRIVEN INVENTORY OPTIMIZATION: HOW PREDICTIVE ANALYTICS IS REVOLUTIONIZING SUPPLY CHAIN MANAGEMENT - Iroda Danabayeva Uktam kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores how predictive analytics and artificial intelligence are transforming inventory management practices across various industries. It examines the technological foundations of AI-driven inventory systems, presents case studies from industry leaders like Nike and Walmart, and offers a phased implementation strategy specifically designed for medium-sized businesses. The paper highlights key success factors including clear objective setting, data quality management, and effective organizational change strategies. The research demonstrates that predictive analytics can deliver substantial improvements in forecasting accuracy, inventory reduction, and cost savings while providing a practical roadmap for businesses looking to adopt these technologies.